Arduino-Based Anti-Theft System in Mosque Charity Box - Bagus Tri Syahputra (Brilliance: Research of Artificial Intelligence, 2022)
The high level of criminal cases makes people have to be more vigilant. One of them is theft. Theft does not only occur in private areas such as homes, but often occurs in public locations, namely places of worship. There are many cases of theft of charity boxes at mosques or other places of worship. In this study, a security system was designed that was applied to the charity box. This tool is expected to reduce the rate of loss of donations in charity boxes. The charity box has an RFID sensor installed to unlock it and a motion sensor to detect movement if a thief tries to unlock the box.